Ovulation and ovulation rate in ewes under grazing conditions: factors affecting the response to short-term supplementation - Banchero, G.E.; Stefanova, Katia; Lindsay, D.R.; Quintans, G.; Baldi, F.; Milton, J.T.B.; Martin, G.B. (EDP Sciences, 2020)
The relationships between ovulation rate and nutrition remain confused, probably because of uncontrolled variation in experimental conditions. To help resolve the problem, we analyzed data from 20 experiments conducted between 2002 and 2016, in Uruguay with grazing ewes. All experiments were carried out by a single laboratory under comparable conditions of experimental design and measured variables. The studies used a total of 3 720 ewes, of purebred Corriedale, Polwarth, or East Friesian x Polwarth genotypes. In all experiments, a control group grazed native pastures and extra nutrition was provided to the treatment groups using either improved pastures or supplements. Ovulation rate was measured by counting corpora lutea using laparoscopy or rectal ultrasound or by counting foetuses at ultrasound on day 45 of gestation. For statistical analysis, data were grouped according to nutritional treatment (control or supplemented) and, within these groups, type of supplement to provide energy or protein (protected or not from rumen degradation). Across all experiments, 92–99% of the ewes ovulated and the effects of diet, length of supplementation, and initial live weight and genotype are reported. Within diets, ovulation was most affected by overall energy intake during supplementation (P < 0.01). Ewes that grazed native pastures supplemented with protein supplements had higher ovulation rates (P < 0.05) than control ewes grazing only native pastures. The addition of tannins to the protein supplement, to protect it from degradation in the rumen, did not further increase the ovulation rate. In unsupplemented ewes that had access to legume pastures, ovulation rates did not increase when the legume pasture was rich in tannins although only ewes that grazed tanniniferous legumes had marginally higher ovulation rates than the control ewes (P < 0.05). When ewes grazing native pastures were supplemented with energy, their ovulation rate did not increase above those of nonsupplemented ewes. Live weight at the start of supplementation also affected ovulation rate. We conclude that ovulation was most affected by overall energy intake, whereas the factors that affected ovulation rate during short-tern nutritional supplementation were intake of protein from highly digested supplements or dietary protein protected from ruminal degradation.